Dominance behaviour of Macrotermes Gilvus, Globitertnes Sulphureus and Odontotermes Sarawakensis towards commercial wood (rubber wood) - Noor Shuhada Ezzatie Mad Daud (2020)
The objective of this study is to determine the dominance behaviour of Macrotermes gilvus, Globitermes sulphureus and Odontotermes sarawakensis towards the commercial wood which was rubber wood. A total number of 50 termites from two different species were placed in a linear bioassay design and were exposed to rubber wood cube for seven days or a week. Wood consumption of termites were measured by quantitative measure which was weight loss of wood cubes, percentage of wood weight loss, milligram of wood cubes per number of termite per day and milligram of wood cubes per gram of termite per day. The comparison for the number of survived termites and wood consumption were differentiate by the linear bioassay design. Results shows that there is no significant difference in the mean value for survival rate and wood consumption (P-value > 0.05). After a week of observation, M. gilvus has the highest survival rate among the three species, followed by 0. sarawakensis and lastly G. sulphureus. All of the wood cubes in all arena shows that there is no sign of it were eaten by the termites. However, the weight of the wood cubes decreasing after a week because it decay naturally. This is because rubber wood has high susceptibility to biological degradation. The p-value of survival rate and wood consumption is greater than the significance level so there is no significance different between the means. There is not enough evidence in rejecting hypothesis where the survival rate and the dominancy of a species have no relationship where the means were all equal.